PGR5/PGRL1 and NDH Mediate Far-Red Light-Induced Photoprotection in Response to Chilling Stress in Tomato - Wang, Feng; Yan, Jiarong; Ahammed, Golam Jalal; Wang, Xiujie; Bu, Xin; Xiang, Hengzuo; Li, Yanbing; Lu, Jiazhi; Liu, Yufeng; Qi, Hongyan; Qi, Mingfang; Li, Tianlai (Frontiers in Plant Science, 2020)
Plants experience low ambient temperature and low red to far-red ratios (L-R/FR) of light due to vegetative shading and longer twilight durations in cool seasons. Low temperature induce photoinhibition through inactivation of the photosynthetic apparatus, however, the role of light quality on photoprotection during cold stress remains poorly understood. Here, we report that L-R/FR significantly prevents the overreduction of the entire intersystem electron transfer chain and the limitation of photosystem I (PSI) acceptor side, eventually alleviating the cold-induced photoinhibition. During cold stress, L-R/FR activated cyclic electron flow (CEF), enhanced protonation of PSII subunit S (PsbS) and de-epoxidation state of the xanthophyll cycle, and promoted energy-dependent quenching (qE) component of non-photochemical quenching (NPQ), enzyme activity of Foyer-Halliwell-Asada cycle and D1 proteins accumulation. However, L-R/FR –induced photoprotection pathways were compromised in tomato PROTON GRADIENT REGULATION5 (PGR5) and PGR5-LIKE PHOTOSYNTHETIC PHENOTYPE1A (PGRL1A) co-silenced plants and NADH DEHYDROGENASE-LIKE COMPLEX M (NDHM) -silenced plants during cold stress. Our results demonstrate that both PGR5/PGRL1- and NDH-dependent CEF mediate L-R/FR –induced cold tolerance by enhancing the thermal dissipation and the repair of photodamaged PSII, thereby mitigating the overreduction of electron carriers and the accumulation of reactive oxygen species. The study indicates that there is an anterograde link between photoreception and photoprotection in tomato plants during cold stress.